TL glow curve and kinetic of gamma irradiated quartz collected from Rasmada mines of C.G. basin - Kaur, Jagjeet; Suryanarayana, N S; Dubey, Vikas; Shrivas, Rahul; Murthy, K.V.R; Dhoble, S J (Recent Research in Science and Technology, 2012)
Present paper reports the TL glow curve and kinetic parameter of Quartz. The sample of natural quartz collected from Rasmada mines of C.G. basin is irradiated with gamma source. For gamma exposure Co60 gamma source was used and the exposure of 1 hour to 4 hour was given to the sample with dose 0.5kGy to 2 kGy. TL glow for quartz crystal shows the peaks at temperature 242, 256, 250 and 2520C for doses 2kGy to 0.5 kGy respectively. The powder sample shows TL glow peak at 236, 251, 254 and 2530C respectively. The corresponding activation energy and frequency factor is calculated by peak shape method. The activation energy found to be 0.79 eV for powder and 1.26 eV for quartz crystal, frequency factor is found to be 4X108 to 3X1013sec-1. The maximum activation energy is found for quartz crystal with gamma exposure of 2kGy. The sample shows first and second order kinetics. The sample was characterized by XRD. The Induction coupled plasma activated emission spectra (ICP - AES) analysis was done to find out the percentage of elements in the quartz mineral.